Quality and security as key factors in the development of computer audits in higher education institutions - Daisy Imbaquingo; Javier Díaz; José Jácome (OmniaScience, 2024)
Higher Education Institutions (HEIs) need a specialized computer audit method to minimize quality and security risks and facilitate institutional evaluation and accreditation. This study aimed to develop a Computer Audit Method for HEIs (MAIIES) providing methodological support for the computer audit process. The MAIIES method includes planning, execution, communication of results, validation, and follow-up of the audit exercise with 47 activities. The validation phase resulted in an evaluation instrument with 42 variables for quality and 18 for security, forming a multivariate model measuring quality and security dimensions. The model comprises factors such as human, technical, contextual, confidentiality, integrity, and availability. The MAIIES method provides a comprehensive audit framework, facilitating compliance with quality and security standards and identifying areas of improvement. It offers a strategic approach for minimizing quality and security risks in HEIs through a comprehensive computer audit process, enabling institutional evaluation and accreditation by ensuring compliance with quality and security standards and identifying areas of improvement.